Real boys' voices - Pollack, William S.; Shuster, Todd. (New York Penguin Books, 2001)
Captures boys speaking out about drugs, sex, sports, violence, ambition, school, and other topics.
Introduction: Listening to Boys' Voices -- A Nationwide Journey -- Moments of Doubt -- Helping Boys to Be Themselves -- Reaching Out and Listening to Boys: A New Approach -- Getting Behind the Mask -- The Real Boys' Voices Project -- Part I. The Secret Emotional Lives of Boys -- 1. The Secret Emotional Lives of America's Boys: What They're Really Talking About -- 2. Taking Off the Gender Straitjacket -- 3. The Mask of Masculinity and the Double Life: Suppression and Bravado -- 4. The Angst of Becoming a Man: Coming of Age -- 5. Of Two Minds: Having Sex with Girls -- 6. The Pressure to Work and Succeed -- 7. Spirituality and Renewal -- 8. Bullying and Teasing: Fitting in and Being Left Out -- Overcoming Bullying -- What if Your Child is Bullying? -- What Should Boys Who Are Bullied Know? -- 9. Sadness, Depression, and Suicide: Sad Boys or Bad Boys? -- Is He Bad or is He Sad? -- How Do You Tell If a Boy is Depressed? -- Part II. The Cycle of Rage and Violence -- 10. Traumatic Violence: Listening to Boys from Littleton, Colorado -- 11. The Columbine Syndrome: Fear of Violence -- 12. Abuse -- Part III. Boys Reaching out and Connecting -- 13. Love for Mother -- 14. The Dad Connection -- 15. Friendships and Romances with Girls -- 16. Having Male Buddies -- 17. Emotional Intensity: Connecting Through Sports -- 18. Coming Out as Gay and Supporting Those Who Do -- Part IV. Dealing with Loss, Loneliness, and Shame -- 19. Pumping and Crunching: Body Image and the Media -- 20. The Sting of Divorce -- 21. Addictions: Drugs, Alcohol, and the Media -- 22. Loss: Coping with Injury, Illness, and Death -- Part V. Boys in the World -- 23. Overcoming Hatred, Racism, and Poverty: Justice and Action Talk -- 24. Music, Art, and Writing: Boys Talk Through Creativity -- Epilogue: Mentoring Boys and Creating Safe Spaces: A 15-Step Program.
Keywords: Boys -- United States -- Attitudes